Analytical Methods for the Measurement of Catechol-O-Methyltransferase Activity in Animal Tissues - Tsunoda, Makoto Tsunoda (Current Biotechnology, 2015)
Catechol-O-methyltransferase (COMT) catalyzes the transfer of a methyl group from Sadenosyl- L-methionine to catechols. Because COMT has an important role in the metabolism of catecholamines, catechol estrogens, and drugs with a catechol moiety such as L-Dopa, measurement of COMT activity in several tissues is important. Furthermore, COMT inhibitors are used clinically in the treatment of Parkinson’s disease, and activation of COMT can control high blood pressure. Hence, high-throughput screening methods for COMT inhibitors and activators are needed. In this methodological article, two analytical methods for the measurement of COMT activity are described. One is very sensitive, and the other is a rapid assay. Norepinephrine, an endogenous compound was used as the substrate, and the enzymatic product (normetanephrine) was quantified with highperformance liquid chromatography-fluorescence or chemiluminescence detection.
Keywords: fluorescence